Daya Saing Kacang Mete Indonesia Di Pasar Negara Tujuan Ekspor - Suharno; Safriadi, Agus; Adhi, Andriyono Kilat (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
Cashew nuts (Anacardium occidentale) are a leading plantation commodity with high economic value, essential for the development of the agricultural industry. Despite their significant potential as an export commodity, the export value of Indonesian cashew nuts has tended to decline during the period from 2013 to 2022. The aim of this study is to measure the competitiveness and development position of Indonesian cashew nuts from 2013 to 2022 in export destination countries. The data used in this research are secondary data in the form of time series data. The time series data includes annual data over 10 years (2013-2022) with export destination countries being Vietnam, India, Malaysia, Singapore, Sri Lanka, Japan, and China. The methods used in this study are the Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and X-Model Potential Export Product methods. The results of the study show the Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) values of Indonesian cashew nuts for the period 2013-2022 in the Vietnamese market with an RCA of 4.47 and a Lost Opportunity market position, India at 0.88 with a Retreat status, Singapore at 0.019 with a Falling Star status, Malaysia at 0.43 with a Lost Opportunity status, Sri Lanka at 21.55 with a Falling Star status, Japan at 7.36 with a Falling Star status, and China at 0.21 with a Rising Star market position. Meanwhile, the X-Model analysis shows that the market potential in Vietnam, Singapore, Sri Lanka, Japan, and Malaysia is classified as potential markets, the market potential in China is classified as an optimistic market, and the market potential in India is classified as a less potential market. As an export commodity, cashew nuts require proper handling and special attention. To ensure the quality, selling value, and strong competitiveness of cashew nuts, the government must continuously strive to enhance the selling value of cashew nuts through plantation development, garden and plant maintenance, and processing improvements.